2014
DOI: 10.1002/mgg3.66
|View full text |Cite
|
Sign up to set email alerts
|

Novel IRF6 mutations in families with Van Der Woude syndrome and popliteal pterygium syndrome from sub‐Saharan Africa

Abstract: Orofacial clefts (OFC) are complex genetic traits that are often classified as syndromic or nonsyndromic clefts. Currently, there are over 500 types of syndromic clefts in the Online Mendelian Inheritance in Man (OMIM) database, of which Van der Woude syndrome (VWS) is one of the most common (accounting for 2% of all OFC). Popliteal pterygium syndrome (PPS) is considered to be a more severe form of VWS. Mutations in the IRF6 gene have been reported worldwide to cause VWS and PPS. Here, we report studies of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 19 publications
2
27
2
Order By: Relevance
“…2009; Butali et al. 2014a). This observation is relevant for genetic testing in Africa: with limited resources, one can focus on exons 4 and 7 when the need arises to sequence the DNA of a subject.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2009; Butali et al. 2014a). This observation is relevant for genetic testing in Africa: with limited resources, one can focus on exons 4 and 7 when the need arises to sequence the DNA of a subject.…”
Section: Discussionmentioning
confidence: 99%
“…2009; Butali et al. 2014a,b). All DNA processing protocols, PCR conditions and electrophoretic procedure are available at the Murray laboratory website (http://genetics.uiowa.edu/protocols.php).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first genetic study on nonsyndromic clefts in sub‐Saharan Africa was conducted in a Nigerian population (Butali et al., ). Subsequent studies from the same research group investigated rare variants in African populations by sequencing GWAS‐identified loci for orofacial clefts (Butali et al., , ,b; Eshete et al., ; Gowans et al., ). The investigators also reported novel IRF6 mutations in families with Van Der Woude syndrome and popliteal pterygium syndrome from sub‐Saharan Africa (Butali et al., ,b).…”
Section: Genetics Research In Nigeriamentioning
confidence: 99%